HZE Radiation Non-Targeted Effects on the Microenvironment That Mediate Mammary Carcinogenesis - Barcellos-Hoff, Mary Helen; Mao, Jian-Hua (Frontiers in Oncology, 2016)
Clear mechanistic understanding of the biological processes elicited by radiation that increase cancer risk can be used to inform prediction of health consequences of medical uses, such as radiotherapy, or occupational exposures such as those of astronauts during deep space travel. Here we review the current concepts of carcinogenesis as a multicellular process during which transformed cells escape normal tissue controls, including the immune system, and establish a tumor microenvironment. We discuss the contribution of two broad classes of radiation effects that may increase cancer: radiation targeted effects (RTE) that occur as a result of direct energy deposition, e.g. DNA damage, and non-targeted effects (NTE) that result from changes in cell signaling, e.g. genomic instability. It is unknown whether the potentially greater carcinogenic effect of HZE particle radiation is a function of the relative contribution or extent of NTE, or due to unique NTE. We addressed this problem using a radiation/genetic mammary chimera mouse model of breast cancer. Our experiments suggest that NTE promote more aggressive cancers, as evidenced by increased growth rate, transcriptomic signatures and metastasis, and that HZE particle NTE are more effective than reference γ-radiation. Emerging evidence suggest that HZE irradiation dampens anti-tumor immunity. These studies raise concern that HZE radiation exposure not only increases the likelihood of developing cancer but also could promote progression to more aggressive cancer with a greater risk of mortality.